Association between obesity and atopic dermatitis in children: A case‐control study in a high obesity prevalence population. Issue 1 (1st September 2022) - Iturriaga, Carolina; Bustos, María Francisca; Le Roy, Catalina; Rodríguez, Rocío; Cifuentes, Lorena; Silva‐Valenzuela, Sergio; Vera‐Kellet, Cristián; Cristi, Francisca; Pérez‐Mateluna, Guillermo; Cabalín, Carolina; Hoyos‐Bachiloglu, Rodrigo; Camargo, Carlos A.; et al.
Abstract: Background/Objective: Atopic dermatitis (AD) is a chronic inflammatory skin disease. Research suggests an association between obesity and AD, although evidence is lacking from Latin American populations. This study evaluated the association of obesity with AD in children from Chile, a country with high obesity prevalence. Methods: A case‐control study was performed in children with active AD (cases) and healthy controls (HCs) from Santiago, Chile. Body mass index was evaluated by z‐score (z‐BMI), with overweight defined as z‐BMI ≥+1 and <+2, and obesity as z‐BMI ≥+2. Abdominal obesity was defined by a waist circumference‐to‐height ratio (WHR) ≥0.5. AD severity was evaluated by Scoring AD (SCORAD) index. Results: A total of 174 children with AD and 101 controls were included. AD patients had similar overweight (27% vs. 28%) and obesity (21% vs. 26%) rates as HCs ( p  = .65). Abdominal obesity rates were also comparable (64% vs. 62%, p  = .81). In sex‐specific analyses, girls with AD had higher abdominal obesity rates than HCs (71% vs. 53%, p  < .05) while boys with AD had lower abdominal obesity rates than HCs (53% vs. 75%, p  = .03). Among children with AD, higher z‐BMI or WHR did not correlate with higher SCORAD, eosinophil counts or total IgE. Conclusion: In our study, Chilean children with AD had high but similar rates of obesity as HCs, but showed sex‐specific associations of abdominal obesity and AD. Further research is needed to evaluate these associations and the roles that weight excess and weight loss could play in the pathogenesis and treatment of AD.